The Characteristics of Tremor Motion Help Identify Parkinson's Disease and Multiple System Atrophy - Su, Dongning; Yang, Shuo; Hu, Wanli; Wang, Dongxu; Kou, Wenyi; Liu, Zhu; Wang, Xuemei; Wang, Ying; Ma, Huizi; Sui, Yunpeng; Zhou, Junhong; Pan, Hua; et al. (Frontiers in Neurology, 2020)
Background/Objectives: Distinguishing between Parkinson’s disease (PD) and multiple system atrophy (MSA) is challenging in the clinic because patients with these two conditions present similar symptoms in motor dysfunction. Here, we aimed to determine whether tremor characteristics can serve as novel markers for distinguishing the two conditions. Methods: Ninety-one subjects with clinically-diagnosed PD and 93 subjects with MSA were included. Tremor of the limbs was measured in different conditions i.e., resting, postural and weight-holding) using electromyography (EMG) surface electrodes and accelerometers. The dominant frequency, tremor occurrence rate and harmonic occurrence rate (HOR) of the tremor were then calculated. Results: Our results demonstrated that the tremor dominant frequency in the upper limbs of the MSA group was significantly higher than that in the PD group across all resting (F=5.717, p=0.023), postural (F=13.409, p<0.001) and weight-holding conditions (F=9.491, p<0.001) and that it was not dependent on the patient’s age or disease course. The tremor occurrence rate (75.6% vs 14.9%, χ2=68.487, p<0.001) and HOR (75.0% vs 4.5%, χ2=46.619, p<0.001) in the resting condition were significantly lower in the MSA group than in the PD group. The sensitivity of the harmonic for PD diagnosis was 75.0%, and the specificity was relatively high, as high as 95.5%. The PPV and NPV were 95.2% and 75.9%, respectively. Conclusion: Our study confirmed that several tremor characteristics, including the dominant tremor frequency and the occurrence rate in different conditions, help detect PD and MSA. The presence of harmonics may serve as a novel marker to help distinguish PD from MSA with high sensitivity and specificity.